Religion in environmental and climate change: suffering, values, lifestyles - Gerten, Dieter; Bergmann, Sigurd (Continuum, 2012)
Acknowledgements -- Notes on Contributors -- Part I: Setting the Stage -- 1. Facing the Human Faces of Climate Change Dieter Gerten & Sigurd Bergmann -- 2. Global Change and the Need for New Cosmologies Wolfgang Lucht -- 3. Religion in the Public Sphere: The Social Function of Religion in the Context of Climate and Development Policy Michael Reder -- 4. Contemplating Climategate: Religion and the Future of Climate Research Timothy Leduc -- Part II: Sketching Sustainable Futures: Recent Dynamics in World Religions -- 5. Climate Justice from a Christian Point of View: Challenges for a new Definition of Wealth Markus Vogt -- 6.Climate Justice and the Intrinsic Value of Creation: The Christian Understanding of Creation and its Holistic Implications Friedrich Lohmann -- 7. Evangelicals and Climate Change Michael Roberts -- 8. Religious Climate Activism in the United States Laurel Kearns -- 9. The Future of Faith: Climate Change and the Fate of Religions Martin Sch nfeld -- Part III: Regional and Indigenous Belief Systems and Environmental Change: Case Studies -- 10. Climate and Cosmology: Exploring Sakha Belief and the Local Effects of Unprecedented Change in North-Eastern Siberia, Russia Susan Crate -- 11. Religious Perspectives on Climate Change Among Indigenous Communities: Questions and Challenges for Ethnological Research Lioba Rossbach de Olmos -- 12. Vulnerable Coastal regions: Indigenous People Under Climate Change in Indonesia Urte Undine Fr mming and Christian Reichel -- 13. Jaichylyk: Harmonizing the Will of Nature and Human Needs Gulnara Aitpaeva -- 14. Environment, Climate and Religion in Ancient European History Holger Sonnabend -- Index.